Negative impact of a dysfunctional family on adolescents: A literature study - Jannah, Miftahul; Hariastuti, Retno Tri; Nursalim, Mochamad (Program Pascasarjana Universitas Negeri Yogyakarta, 2023)
This research aims to educate parents, teachers, and adolescents about some of the negative impacts of family dysfunction. This research used the journal literature study method. Data was collected from journal sites accessed online and downloaded in full-text versions. The journal articles were published in journals within the last five years, from 2018 to 2022. Data sources in the form of journal articles were obtained from the Google Scholar database. This research explores the negative impact of family dysfunction. The initial search yielded 12,900 journal articles, which were then reduced to 6,480 articles using specific keywords. The analysis in this study was conducted using descriptive analysis techniques. The results showed seven impacts of family dysfunction: low academic achievement, loneliness, bad behavior, envy, low self-esteem, low self-confidence, damage to social relationships (both in economic and recreational functions), and mental disorders.